Silver - Kidd, Rob; Orpinas, Jean-Paul (New York : Disney Press, 2007)
After Jack Sparrow and his crew get aboard the Fleur de la Mort, they find that it will be much more difficult to leave this ship
"Based on the earlier life of the character, Jack Sparrow, created for the theatrical motion picture, 'Pirates of the Caribbean: the curse of the black pearl .... and characters created for the theatrical motion pictures 'Pirates of the Caribbean: dead man's chest' and 'Pirates of the Caribbean 3'."
Keywords: Sparrow, Jack (Fictitious character) -- Juvenile fiction; Pirates -- Juvenile fiction; Ships -- Juvenile fiction; Adventure stories; Sparrow, Jack (Fictitious character) -- Fiction; Pirates -- Fiction; Ships -- Fiction; Adventure and adventurers -- Fiction; Adventure stories; Pirates; Ships; Sparrow, Jack (Fictitious character); Adventure fiction; Movie novels; Fiction; Juvenile works